Service provision for children and young people with acquired brain injury: Practice recommendations. (5th December 2016) - McKinlay, Audrey; Linden, Mark; DePompei, Roberta; Aaro Jonsson, Catherine; Anderson, Vicki; Braga, Lucia; Castelli, Enrico; de Koning, Peter; Hawley, Carol A.; Hermans, Eric; Kristiansen, Ingela; Madden, Alison; et al.
Abstract: Background : Providing appropriate rehabilitation services for Acquired Brain Injury (ABI) in childhood presents a number of challenges for caregivers, health and education professionals and the young person as they develop. Primary objective : To record the challenges and possible creative solutions generated by an international group of professionals to address the needs of children with ABI. Review of information : Recommendations were generated from children's special interest group meetings of the International Brain Injury Association (Turin, Italy, 2001; Stockholm, Sweden, 2003; Melbourne, Australia, 2005; Lisbon, Portugal, 2008) and through meetings of the International Paediatric Brain Injury Society (IPBIS), formed in 2009. Delegates participating in the workshops were representative of nations from around the world and included The Netherlands, New Zealand, Australia, the UK, Finland, Germany, South Africa, the US, Canada, Sweden, Brazil and Italy. Outcomes : The information presented is based on a retrospective review of those meetings and the summaries of the topics considered.